2023
DOI: 10.3390/nano13020341
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Individual and Simultaneous Adsorption of Antibiotics and Dyes onto Halloysite Nanoclay and Regeneration of Saturated Adsorbent via Cold Plasma Bubbling

Abstract: Halloysite nanoclay (HNC) was examined as an adsorbent for the individual and simultaneous removal of antibiotic enrofloxacin (ENRO) and methylene blue (MB) from aqueous solutions, alongside its regeneration via cold atmospheric plasma (CAP) bubbling. Initially, batch kinetics and isotherm studies were carried out, while the effect of several parameters was evaluated. Both ENRO and MB adsorption onto HNC was better described by Langmuir model, with its maximum adsorption capacity being 34.80 and 27.66 mg/g, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 81 publications
0
1
0
Order By: Relevance
“…Energy-dispersive X-ray (EDX) analysis corroborated the presence of significant levels of carbon, nitrogen, oxygen, and calcium, with metallic nanoparticles visible in the spectra. This confirmed the composite hydrogel's capacity to bind and potentially load antibiotics, showcasing its utility in purifying water (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Energy-dispersive X-ray (EDX) analysis corroborated the presence of significant levels of carbon, nitrogen, oxygen, and calcium, with metallic nanoparticles visible in the spectra. This confirmed the composite hydrogel's capacity to bind and potentially load antibiotics, showcasing its utility in purifying water (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 54%
“…The surface morphology was meticulously analyzed using a Field Emission Scanning Electron Microscope (FESEM), revealing a rough and porous texture, ideal for trapping impurities through complexation and hydrogen bonding (17)(18)(19)(20). The freeze-drying preparation of the samples, followed by sputter-gold coating, provided an in-depth examination of the hydrogel's internal structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This 1indicates that there are other mechanisms that are involved in the adsorption process, which are rate-limiting, in 2 addition to pore diffusion. Along with intraparticle diffusion, another mechanism might be involved during the 3 entire adsorption process(Giannoulia et al, 2023) 4 5 6…”
mentioning
confidence: 99%
“…These authors concluded that Ag 3 PO 4 –based materials could be reliably used for the degradation of methyl orange (MO) as they mostly retain their photoactivity during the second recycling test. In the final paper by Giannoulia et al [ 21 ], halloysite nanoclay (HNC) was examined as an adsorbent for the individual and simultaneous removal of antibiotic enrofloxacin (ENRO) and methylene blue (MB) from aqueous solutions, alongside its successful regeneration via cold atmospheric plasma (CAP) bubbling. In addition, CAP bubbling induced chemical modifications on the HNC surface, increasing its adsorption capacity when applied to new adsorption cycles.…”
mentioning
confidence: 99%